1985
DOI: 10.1055/s-2008-1025838
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Maximal Effort Bicycle Ergometer Endurance Performance

Abstract: Fifteen competitive cyclists and 15 subjects not involved in competitive cycling were studied to determine the relationship between VO2max, lactate threshold (LT), fixed blood lactate concentrations, body composition parameters, and maximal effort bicycle ergometer performance. The subjects were assessed for VO2max, LT, VOLT, and VO2 associated with blood lactate concentrations of 3, 4, 5, and 6 mM/l (VO2 3 mM-VO2 6 mM/l), using an incremental protocol on the bicycle ergometer. Body composition was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Maximal oxygen consumption (V O zmax) has traditionally been used as the criterion measure o f endurance performance (Astrand and Rodahl, 1986;Bassett and Howley, 2000;Costill, 1967;Coyle et al, 1988;Craig, et al, 1993;Foster, 1978;Hagberg and Coyle, 1983;Hill and Lupton, 1923;Noakes, 1988;Saltin and Astrand, 1967;Sleivert and Rowlands, 1996). However, several investigators have recently suggested that physiological parameters measured during submaximal exercise may provide better predictors o f endurance performance than V OiMAx-These parameters include blood lactate transition thresholds (Barlow et al, 1985;Coyle, et al, 1991;Craig, et al, 1993;Farrell, et al 1979;Hagberg and Coyle, 1983;Hopkins and McKenzie, 1994;Jacobs, 1986;Loftin and Warren, 1994;Miller and Manfredi, 1987;Powers et al, 1983;Schabort et al, 2000;Sjodin, 1981;Yoshida et al, 1987) and economy o f movement (Conley and Krahenbahl51980;Costill et al, 1985;Powers et al,1983;Schabort et al, 2000).…”
Section: Physiological Determinants O F Endurance Performancementioning
confidence: 99%
“…Maximal oxygen consumption (V O zmax) has traditionally been used as the criterion measure o f endurance performance (Astrand and Rodahl, 1986;Bassett and Howley, 2000;Costill, 1967;Coyle et al, 1988;Craig, et al, 1993;Foster, 1978;Hagberg and Coyle, 1983;Hill and Lupton, 1923;Noakes, 1988;Saltin and Astrand, 1967;Sleivert and Rowlands, 1996). However, several investigators have recently suggested that physiological parameters measured during submaximal exercise may provide better predictors o f endurance performance than V OiMAx-These parameters include blood lactate transition thresholds (Barlow et al, 1985;Coyle, et al, 1991;Craig, et al, 1993;Farrell, et al 1979;Hagberg and Coyle, 1983;Hopkins and McKenzie, 1994;Jacobs, 1986;Loftin and Warren, 1994;Miller and Manfredi, 1987;Powers et al, 1983;Schabort et al, 2000;Sjodin, 1981;Yoshida et al, 1987) and economy o f movement (Conley and Krahenbahl51980;Costill et al, 1985;Powers et al,1983;Schabort et al, 2000).…”
Section: Physiological Determinants O F Endurance Performancementioning
confidence: 99%